ISLAM AND INDONESIA IN VIEWS OF NAHDLATUL ULAMA AND PERSATUAN ISLAM - Imanuddin Abil Fida (LPPM STAI Muhammadiyah Probolinggo, 2018)
The legal debate pertaining to the position of Islam di Indonesia has been emerged from the beginning of freedom hassle of Indonesia. Each leader and religious organization has the difference thought including Nahdlatul Ulama and Persatuan Islam. One of the difference was to what extent Indonesian Muslims stand of nationalism between Tauhid and the obligation of worship. Each has the dissimilar thought which has implications to their participation in Indonesian politics since the beginning of Indonesian freedom until New Order era. This article will discuss the difference thought between two organizations following some historical facts of their difference